Research trends in employee motivation in remote work condition: a bibliometric analysis - P. Gao; B. Turebekova; A. Kłoczko-Gajewska (Хабаршысы. Экономика сериясы)
The COVID-19 pandemic has not only fundamentally transformed organizational practices, but leading to an unprecedented shift toward remote work at the same time. This study focuses on understanding the relationship between remote work and employee motivation, which has attracted increased interests in the post-pandemic era. The purpose of this study is to conduct a bibliometric review of the literature, highlighting key research trends, central themes, and influential contributions in this field.